Reevaluating the Necessity of a State of Emergency: Lessons from the Covid-19 Pandemic - Taqwa, Muhamad Dzadit; Al Bone, Nayla Amalia (Fakultas Hukum Universitas Lampung, 2024)
Jimly Asshiddiqie argued that Indonesia should have declared a state of emergency during COVID-19 to ensure effective governance, asserting that, without it, the government lacked legitimacy to implement restrictive policies. This paper critically examines this claim through a doctrinal and regulatory policy analysis, assessing the necessity of an emergency declaration in managing the pandemic. The research evaluates regulatory effectiveness, legal implications, constitutional rights restrictions, and governmental legitimacy. While a state of emergency could enhance policy enforcement, the government retained legitimacy to implement necessary measures without it. Moreover, invoking Article 12 of the 1945 Constitution could have worsened the situation due to its broad legal consequences. However, the absence of an emergency declaration did not necessarily lead to a more effective response, as the government’s initial inaction and public unpreparedness contributed to financial difficulties. Ultimately, Indonesia managed to conclude the pandemic without declaring a state of emergency..